Comparative efficacy of Gum Arabic (Acacia senegal) and Tribulus terrestris on male fertility - Omaima Nasir; Nada Alqadri; Salma Elsayed; Omaima Ahmed; S.H. Alotaibi; Roua Baty; Hiba Omer; Suzan A. Abushal; Anja T Umbach (Elsevier, 2020)
In this study the effect of Gum arabic (Acacia Senegal) was systemically targeted at male fertility with two experiments, the first comparing the effectiveness of Gum arabic (GA) and Tribulus terrestris (TT). For the first experiment, 27 adult mice Balb / c (18 females, 9 males) were divided into 3 in each group, one male and two females, group one had the usual tap water as power, group two had 5% (w / v) GA and group three had 5% (w / v) of TT for 21 days. The results showed, the number of offspring was more with GA treated when compared to TT treated. Blood measurements of testosterone showed significant increase in the GA group as compared to other groups, also Histopathological analysis showed the dose dependent 5% GA had normal seminiferous tubules with increase spermatogenesis. In this study the enhanced fertility in GA-treated mice Balb/c was observed and the experimental studies also show that GA fertility was increased.